Bone morphogenetic proteins in inflammation, glucose homeostasis and adipose tissue energy metabolism. (February 2016) - Grgurevic, Lovorka; Christensen, Gitte Lund; Schulz, Tim J.; Vukicevic, Slobodan
Graphical abstract: Highlights: BMPs mediate inflammatory processes in the gastrointestinal system, skeletal and cardiovascular diseases. BMPs affect systemic energy balance by targeting the pancreas as well as brown and white adipose tissues. BMPs regulate pancreatic development and insulin secretion. BMPs act as inducers of brown adipocyte formation and thermogenic function. Abstract: Bore morphogenetic proteins (BMPs) are members of the transforming growth factor (TGF)-β superfamily, a group of secreted proteins that regulate embryonic development. This review summarizes the effects of BMPs on physiological processes not exclusively linked to the musculoskeletal system. Specifically, we focus on the involvement of BMPs in inflammatory disorders, e.g. fibrosis, inflammatory bowel disease, anchylosing spondylitis, rheumatoid arthritis. Moreover, we discuss the role of BMPs in the context of vascular disorders, and explore the role of these signalling proteins in iron homeostasis (anaemia, hemochromatosis) and oxidative damage. The second and third parts of this review focus on BMPs in the development of metabolic pathologies such as type-2 diabetes mellitus and obesity. The pancreatic beta cells are the sole source of the hormone insulin and BMPs have recently been implicated in pancreas development as well as control of adult glucose homeostasis. Lastly, we review the recently recognized role of BMPs in brown adipose tissue formation and their consequences for energy expenditure and adiposity. In summary, BMPs play a pivotal role in metabolism beyond their role in skeletal homeostasis. However, increased understanding of these pleiotropic functions also highlights the necessity of tissue-specific strategies when harnessing BMP action as a therapeutic target.